Dying in the Intensive Care Unit: A Candle Vigil Using Illustrations - Elizabeth K.N. Johnson, RN, BSN; Eelco F.M. Wijdicks, MD, PhD (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2018)
With death and dying in intensive care units, there should be bereavement support for families. We propose placing an illustration of a candle on the door of an unresponsive dying patient, with additional illustrations of votive candles at the nurses’ station opposite to the door as a neutral way of identifying these rooms with patients who transitioned to comfort care or who have died. The candle illustrations encourage staff members to modify their words, silence themselves, and reflect. After a 1-year tryout in the neurointensive care unit with a strong positive experience for staff and families, it can be perceived as a symbol of tranquility.